2014
DOI: 10.1371/journal.pone.0103082
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcome after Major Trauma: What Are We Measuring?

Abstract: ImportanceTrauma is a global disease and is among the leading causes of disability in the world. The importance of outcome beyond trauma survival has been recognised over the last decade. Despite this there is no internationally agreed approach for assessment of health outcome and rehabilitation of trauma patients.ObjectiveTo systematically examine to what extent outcomes measures evaluate health outcomes in patients with major trauma.Data SourcesMEDLINE, EMBASE, and CINAHL (from 2006–2012) were searched for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 72 publications
2
63
3
Order By: Relevance
“…However, they concluded that the existing outcome measures did not fully describe the impact of major trauma on function, disability and health. The health outcomes of trauma patients may therefore not be fully understood [27]. The Trauma Outcomes Profile (TOP), a trauma-specific tool, was shown to cover the largest representation of the International Classification of Function, Disability and Health (ICF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they concluded that the existing outcome measures did not fully describe the impact of major trauma on function, disability and health. The health outcomes of trauma patients may therefore not be fully understood [27]. The Trauma Outcomes Profile (TOP), a trauma-specific tool, was shown to cover the largest representation of the International Classification of Function, Disability and Health (ICF).…”
Section: Discussionmentioning
confidence: 99%
“…The TOP may have potential use in trauma population but requires further validation [28]. The outcome evaluation and understanding of the true health impact of injury may be limited due to the lack of an ICF-based framework [27]. …”
Section: Discussionmentioning
confidence: 99%
“…2 These injuries account for the loss of more disability-adjusted life years than any other disease, but many of the instruments and measurements used to assess outcome in this population are non-standardized or are adapted from other populations. 3,4 Additionally, the acute cost associated with each patient, when medical care and work loss are considered, is around $66,150 or $406 billion annually. 1,5 Thus, it is essential that a concerted effort be made to improve post-traumatic quality of life, thereby easing the current and future burden of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of using the TBI ICF Core Sets as a guide for the assessment is that it improves quality assurance of assessing the four different domains that interact in functioning. For example, research has shown that professionals tend to assess according to their area of knowledge (Laxe et al, 2014) and environmental factors that have a significant effect on functioning are not systematically assessed (Hoffman et al, 2014;Laxe et al, 2012).…”
Section: The Clinical Implementation Of Icf In Tbimentioning
confidence: 99%